HUBUNGAN ANTARA KEMAMPUAN KOMUNIKASI MATEMATIS DAN HASIL BELAJAR MATEMATIKA SISWA KELAS V SDN SEKECAMATAN ALIAN - Usvah Istikomah; Wahyudi Wahyudi; Moh. Salimi (Journal of Professional Elementary Education, 2022)
The background of this research is the weak ability of students in communicating their ideas or thoughts into mathematical language with the aim of research (1) to determine the correlation between mathematical communication skills and mathematics learning outcomes about solid figures to fifth grade students of public elementary schools in Alian Sub-district and (2) to measure the contribution of mathematical communication skills on mathematics learning outcomes about solid figures to fifth grade students of public elementary schools in Alian Sub-district in academic year of 2020/2021. The research was correlational quantitative method. The samples were 297 fifth grade students in 11 public elementary schools throughout Alian Sub-district. Data analysis used a simple correlation test with a significance level of 5% and the determination coefficient. The results showed that: (1) there was a correlation between mathematical communication skills and mathematics learning outcomes about solid figures to fifth grade students of public elementary schools in Alian Sub-district. It indicated strong correlation which was the value of r arithmetic (0.538) > r table (0.114). It meant that the higher student’s mathematical communication skills, the higher student’s mathematics learning outcomes, and vice versa; (2) the determination coefficient of mathematical communication skills was 28.9% on mathematics learning outcomes and the remaining 61.1% was influenced by other factors